2002
DOI: 10.1007/s00106-002-0641-9
|View full text |Cite
|
Sign up to set email alerts
|

Rekonstruktion des Steigbügeloberbaus beim Meerschweinchen mit einer Biovitrokeramik und Silikonfolie

Abstract: The guinea pig was not an ideal model for questions of middle ear reconstructions due to its enormous potential for bone formation. In this animal model bony fixation of glass-ceramic with the stapes-footplate could be induced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
4
0
3
Order By: Relevance
“…However, only one research group has dealt with a middle ear model of mice for ossicular chain replacements so far [20][21][22]. Dost et al found new bone formation surrounding Bioverit Õ I þ II, hydroxyapatite and Ceravital Õ implants, and also in contact with the middle ear wall in guinea pigs [18,19,23]. Additionally, a significant amount of new bone around the ossicle was observed in a reconstruction with hydroxyapatite cement and dahllite cement [24].…”
Section: Animal Modelmentioning
confidence: 99%
“…However, only one research group has dealt with a middle ear model of mice for ossicular chain replacements so far [20][21][22]. Dost et al found new bone formation surrounding Bioverit Õ I þ II, hydroxyapatite and Ceravital Õ implants, and also in contact with the middle ear wall in guinea pigs [18,19,23]. Additionally, a significant amount of new bone around the ossicle was observed in a reconstruction with hydroxyapatite cement and dahllite cement [24].…”
Section: Animal Modelmentioning
confidence: 99%
“…Wie auch bei Glaskeramiken findet die Bindung zwischen der Oberfläche und benachbarten Weichteilen über die Ausbildung von Kollagenfasern statt [37] und führt dort zur Osteoneogenese. Dost und Mitarbeiter konnten im Tierversuch auch im Mittelohr bei Verwendung biaoaktiver Ossikelprothesen aus Hydroxylapatit, Glaskeramik (Ceravital ) oder Biovitrokeramik (Bioverit II ) eine Osteoneogenese demonstrieren [47]. Die osteogenetische Potenz des Apatits (BoneSource ) ist im Kulturmodell allerdings niedriger als die von Ethisorb [19].…”
Section: Titannetzeunclassified
“…As with glass ceramics, binding between the surface and neighboring soft tissue occurs via the formation of collagen fibers [37] and leads there to osteoneogenesis. In an animal experiment, Dost and his colleagues demonstrated osteoneogenesis in the middle ear, using bioactive ossicle prostheses made of hydroxylapatit, glass ceramic (Ceravital ® ), or biovitroceramic (Bioverit II ® ) [47]. The osteogenetic potency of apatit (BoneSource ® ) is, however, lower than that of Ethisorb ® in the culture model [19].…”
Section: Hard Tissue Replacementmentioning
confidence: 99%